Does the group matter? Effects of trust, cultural diversity, and group formation on engagement in group work in higher education. Issue 2 (23rd February 2022) - Poort, Irene; Jansen, Ellen; Hofman, Adriaan
ABSTRACT: Group work is a common active learning strategy in higher education when the goal is to enhance deep learning and develop teamwork skills. Culturally diverse learning groups are particularly valuable in preparing university students to participate in a globalized world. Student engagement in group work is critical in realizing these benefits. Therefore, more insight into what factors promote engagement is necessary. This study investigates the extent to which trust in the group, cultural diversity in the group, and group formation contribute to behavioral and cognitive engagement in group work. A questionnaire was filled out by 1025 bachelor's students from six universities in the Netherlands and Canada. Structural equation modeling analyses identified students' trust in the group as the strongest positive predictor of both behavioral and cognitive engagement. Greater perceived cultural diversity was found to promote behavioral and cognitive engagement, but compared with trust, the impacts were relatively small. Whether students could choose their group members did not affect behavioral or cognitive engagement significantly. Contrary to what was expected, trust did not act as a mediator. That is, cultural diversity and group formation did not indirectly affect engagement through trust. These findings prompt some suggestions for how to enhance student engagement in group work.